Variation of depressive and anxiety disorder among government and private old care home residents: a comparative study (Bangladesh Journal of Psychiatry, 2024)
The older population is rapidly growing throughout the world. Though Bangladesh has a long cultural and religious tradition of looking after the elders, but rapid socioeconomic and demographic transitions, mass poverty, changing social and religious values, influence of western culture and other factors have broken down the traditional extended family and community care system. Most of the elderly people in Bangladesh suffer from some basic human problems, such as poor financial support, senile diseases, and absence of proper health and medicine facilities, negligence, deprivation and socioeconomic insecurity. Increase care based on old homes both government and private variation may be more able to improve the quality of life of elderly people as well as old care home residents. This study was done to find out the depressive and anxiety disorder variation among the elderly people living in old care home. This cross-sectional study was conducted from January 2018 to September 2019, among the residents of two different old care homes of Bangladesh.  One was government, run by ministry of social welfare and another was private. Total 138 respondents (20 from government and 118 from private institution) irrespective of their sex were interviewed with a socio-demographic questionnaire at first. Then both structured clinical interview for DSM-IV (SCID) and depression anxiety stress scale (DASS) 21 Bangla version were applied to them to find out the depression and anxiety as well as their severity. The results showed that, the respondents were predominantly male (58.7%). More than half of the respondents were from urban background (52.2%) and most of them came from nuclear family (79.7%). Among the respondents, 10.87% had major depressive disorder, 5.07% had dysthymic disorder, 6.52% had generalized anxiety disorder, 3.62% had panic disorder, 2.17% had social phobia, 1.45% had obsessive compulsive disorder and 0.75 % had specific phobia. Apart from this, 15% of government old care home residents were suffering from any kind of depression, which was 16.1% among private. Also 15.3% old care home residents from private and 10% from government were suffering from any kind of anxiety disorder.  Regarding within level or severity of depression in government old care home residents, it was found normal (22.9%), mild (19.4%), moderate (7.9%), severe (0%), extremely severe (18.8%) which was found in private old care home as normal (77.1%), mild (80.6%), moderate (92.1%), severe (100%), extremely severe (81.2%). According to the level or severity of anxiety in government old care home was found normal (24.4%), mild (17.1%), moderate (4.5%), severe (0%), extremely severe (33.3%). In comparison to private old care home which was found normal (75.6%), mild (82.9%), moderate (95.5%), severe (100%), extremely severe (66.7%). It was seen that depression and anxiety was more common among private old care home residents. Also, Private institution was prone to be associated with all level of depression and anxiety from mild to extremely severe more often than the government.Bang J Psychiatry 2023;37(1): 14-19